AKTIVITAS ANTIOKSIDAN BEKATUL LEBIH TINGGI DARIPADA JUS TOMAT DAN PENURUNAN AKTIVITAS ANTIOKSIDAN SERUM SETELAH INTERVENSI MINUMAN KAYA ANTIOKSIDAN - Evy Damayanthi; Lilik Kustiyah; Mahani Khalid; Henry Farizal (Food and Nutrition Society of Indonesia, 2010)
Recently, many foods were identified contain high antioxidant substances such as tomatoes and rice bran. The objectives of this research were to observe their total antioxidant activity values and the effect of intervention of high-antioxidant beverages (tomato juice and rice bran beverage) to total antioxidant activity on breast cyst women patient’s blood serum. Subject consumed each of the beverages for 14 days. Blood samples were taken before the intervention, at the end of tomato juice intervention period and at the end of rice bran beverage intervention period. Total antioxidant activity on serum was determined by DPPH method. The ascorbic acid equivalent antioxidant capacity (AEAC) of rice bran greater than tomato juice is 28.74 mg/100g and 1.87 mg/100g respectively. The total antioxidant activity on serum was decreasing after tomato juice intervention (p>0.05) but the decreasing of it was significantly shown after rice bran intervention (p<0.05).